Heart Rate Behavior in Speed Climbing - Fuss, Franz Konstantin; Tan, Adin Ming; Pichler, Stefanie; Niegl, Günther; Weizman, Yehuda (Frontiers in Psychology, 2020)
Speed climbing is an Olympic discipline within the combined sport climbing event in 2020 for the first time. Speed climbing is a high-speed, anaerobic and extreme psychological pressure exercise against gravity over a few seconds. Although there is some literature on heart rate (HR) when speed climbing, there is no literature on the behaviour of the HR when speed climbing. The HR of seven participants was measured with a Polar HR monitor while climbing a 10 m and 15 m wall three times each, with pauses of 5 minutes between the first and last three climbs, and a 20 minutes pause between the 3rd and 4th climb. The average climbing time on the 10 m and 15 m walls was 9.16±3.06 s and 14.95±3.14 s. The peak HR on the 10 and 15 m walls was 164.57±7.45 bpm and 176.43±8.09 bpm. The rate of change in HR was: average HR acceleration before peak HR: 2.53±0.80 bpm/s; average HR acceleration before peak HR: 4.16±1.08 bpm/s; average HR deceleration after peak HR: -0.98±0.30 bpm/s. The average HR during the pauses ranged from 105.80 to 117.89 bpm. From the results, in comparison to the literature, we conclude that athletes, trained for sustaining high physical exertion and psychological pressure, have a far smaller HR acceleration than untrained people during light and unstressful exercises. Furthermore, the current rule, that athletes shall have a minimum resting time of five minutes between climbing attempts during a speed climbing competition, seems justified as sufficient time for HR recovery.